2021
DOI: 10.1111/php.13407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of UV‐filter Photostabilizers in the Photostability and Phototoxicity of Vitamin A Palmitate Combined with Avobenzone and Octyl Methoxycinnamate

Abstract: A challenge for cosmetic and dermatologic products is to develop new high‐performance and safer anti‐aging products based on new compounds to enhance the stability of retinyl palmitate combined with broad‐spectrum UV‐filters. Consequently, the aim of this work was to evaluate the effects of three often used avobenzone photostabilizers—ethylhexyl methoxycrylene (EHMCR), tris(tetramethylhydroxypiperidinol) citrate (TTMHP) and tris‐biphenyl triazine (TBPT)—on the photostability and phototoxicity of the combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 58 publications
(87 reference statements)
0
15
0
Order By: Relevance
“…As a result, EHMCR may be used to photostabilize AVOB-OMC formulations with or without RP, whereas TTMHP could be added to this photounstable UV-filter combination. The addition of EHMCR to this mixture increased the photostability of both compounds, resulting in a reduction in phototoxicity [ 85 ].…”
Section: Examples Of Novel Approaches Used For Enhancing the Properti...mentioning
confidence: 99%
“…As a result, EHMCR may be used to photostabilize AVOB-OMC formulations with or without RP, whereas TTMHP could be added to this photounstable UV-filter combination. The addition of EHMCR to this mixture increased the photostability of both compounds, resulting in a reduction in phototoxicity [ 85 ].…”
Section: Examples Of Novel Approaches Used For Enhancing the Properti...mentioning
confidence: 99%
“…Some UV lters available in the market present higher photo-instability than the fractions and isolated compound 6 of this study. Rangel and co-workers (2020), studied the photostability of some UV lters on the market and the results showed that benzophenone-3 presented approximately 30% of UV absorption reduction, and the broadspectrum UV lter avobenzone showed a considerable decrease (about 90% reduction) of UV absorption after exposure to UVA radiation (Rangel et al, 2020;Scarpin et al, 2021).…”
Section: Photostability Studiesmentioning
confidence: 99%
“…[11][12][13][14][15] Researchers have made different proposals to improve the performance of the filters to radiation exposure, such as nano and micro-encapsulation, ROS trappers and inhibitors, and synthesis of new molecules with improved photostability. [16][17][18][19][20][21][22][23][24] Several methods and irradiation sources have been used along the time to study the photostability of different molecules and formulations. ity of the UV filters, which is particularly feeble for the UVA.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have made different proposals to improve the performance of the filters to radiation exposure, such as nano and micro‐encapsulation, ROS trappers and inhibitors, and synthesis of new molecules with improved photostability 16–24 …”
Section: Introductionmentioning
confidence: 99%